Analysis of chemical constituents and six compounds in Qu‐feng‐sheng‐shi Granules via HPLC–ESI–Q/TOF–MSn and HPLC–UV technique. (28th March 2020) - Yang, Pengshuo; Gao, Ruilin; Liu, Ziyao; Qu, Qingsong; Yang, Chang; Shi, Xinyuan; Lian, Zenglin
Abstract: Qu‐feng‐sheng‐shi Granules (QFSSG), a common prescription for the treatment of chronic inflammation and allergic rhinitis, is widely used in the clinic as a traditional Chinese medicine. Chemical analysis and quality control studies of this formulation are relatively limited compared with pharmacological studies. In this study, a high‐performance liquid chromatography coupled with electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry (HPLC–ESI–Q/TOF–MS n ) was used to identify the components in this prescription. Next, to quantify six major compounds, an HPLC–UV method was developed and validated. The results showed that 53 compounds were identified based on the MS n data, retention time and previous reports, including 17 coumarins, 14 lignans, 10 chromones, nine phenylethanoid glycosides and three other compounds, were identified or tentatively assigned. Contents of six major bioactive compounds (4′‐ O ‐ β ‐glucopyranosyl‐5‐ O ‐methylvisamminol, Prim‐ O ‐glucosylcimifugin, forsythin, magnolin, imperatorin, isoimperatorin) could be determined by HPLC simultaneously. In addition, the potential anti‐inflammatory activity of six major compounds was determined too, and we found that four compounds (4′‐ O ‐ β ‐glucopyranosyl‐5‐ O ‐methylvisamminol, Prim‐ O ‐glucosylcimifugin, forsythin, imperatorin) have a potent nitric oxide inhibitory effect. In conclusion, this work provided comprehensive information on the quality control of QFSSG and evaluated the potential biological activity of the main components in QFSSG, which can contribute to understanding and using it more scientifically.